Protocol of the use of orthodontic wires in self-ligating appliances (Research, Society and Development, 2021)
Due to the wide variety of manufacturers of self-ligating orthodontic appliances, doubts regarding the protocol of use and the sequence of the archwires in these appliances may arise. In this way, the knowledge of the mechanical properties of orthodontic wires facilitates the most appropriate choice for each phase of treatments. The technological evolution of the manufacture of the wires and the development of new orthodontic techniques lead to a search for a better quality of the alloys, in order to make them biologically more effective with regard to the teeth and supporting tissues. This work presents the wire protocol for each treatment phase; the wire protocol recommended by different manufacturers and the Bioforce archwire protocol used at the FAIPE clinic.